Ghrelin Through GHSR1a and OX1R Heterodimers Reveals a Gαs–cAMP-cAMP Response Element Binding Protein Signaling Pathway in Vitro - Xue, Qingjie; Bai, Bo; Ji, Bingyuan; Chen, Xiaoyu; Wang, Chunmei; Wang, Peixiang; Yang, Chunqing; Zhang, Rumin; Jiang, Yunlu; Pan, Yanyou; Cheng, Baohua; Chen, Jing (Frontiers in Molecular Neuroscience, 2018)
Growth hormone secretagogue receptor 1α (GHSR1a) and Orexin 1 receptor (OX1R) are involved in various important physiological processes, and have many similar characteristics in function and distribution in peripheral tissues and the central nervous system. We explored the possibility of heterodimerization between GHSR1a and OX1R and revealed a signal transduction pathway mechanism. In this study, bioluminescence and fluorescence resonance energy transfer and co-immunoprecipitation (Co-IP) analyses were performed to demonstrate the formation of functional GHSR1a/OX1R heterodimers. This showed that a peptide corresponding to the 5-transmembrane domain of OX1R impaired heterodimer construction. We found that ghrelin stimulated GHSR1a / OX1R heterodimer cells to increase the activation of Gαs protein, compared to the cells that express GHSR1a. Stimulation of GHSR1a/OX1R heterodimers with orexin-A did not alter GPCR interactions with Gα protein subunits. GHSR1a/OX1R heterodimers induced Gαs and downstream signalling pathway activity, including increase of cAMP-response element luciferase reporter activity and cAMP levels. In addition, ghrelin induced a higher proliferation rate in SH-SY5Y cells than in controls. This suggests that ghrelin GHSR1a/OX1R heterodimers promotes an upregulation of a Gαs-cAMP-cAMP-responsive element signalling pathway in vitro and an increase in neuroblastoma cell proliferation.